Raphael Semmes papers - Semmes, Raphael, 1786-1846.
Correspondence and other documents relating to land transactions in Charles County, Md. Correspondents include Edward Brawner, Alexander Gray, Samuel Hanson, and Henry Posey.
Landowner of Charles County, Md., and Georgetown, D.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brawner, Edward -- Correspondence; Gray, Alexander -- Correspondence; Hanson, Samuel -- Correspondence; Posey, Henry -- Correspondence; Land tenure -- Maryland -- Charles County; Landowners